Evaluation of the Achievement of National Regency/City Library Standards at the Surabaya City Library and Archives Service - Syan, Hidayati; Kriswibowo, Arimurti (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
The library of the District/City is likened to a university for the community, playing a role in enlightening the lives of all layers of society. This research aims to understand and describe the results of the implementation of the National Standards for District/City Libraries (SNP District/City) in the Surabaya City Library and Archives Department. at the Dinas Perpustakaan dan Kearsipan Kota Surabaya. This research uses a mixed method with the convergent parallel design. Data for this study were obtained through observation, interviews, and indicators related to SNP Kabupaten/Kota. The study shows that the results of the implementation of SNP District/City in the Dinas Perpustakaan and Kearsipan Surabaya City are quite good, with an average achievement score of 73% of the specified standards. Library management standards achieved the highest score at 94%, while library service standards received the lowest score at 55% of the qualification of SNP Kabupaten/Kota